Ukraine is not dead yet : a family story of exile and return - Buskey, Megan (Ukrainian voices (Stuttgart, Germany), 2023)
"When Megan Buskey's grandmother Anna dies in Cleveland in 2013, Megan is compelled in her grief to uncover and document her grandmother's life as a native of Ukraine. A Ukrainian American, Buskey returns to her family's homeland and enlists her relatives there to help her in her quest--and discovers much more than she expected. The result is an extraordinary journey that traces one woman's story across Ukraine's difficult twentieth century, from a Galician village emerging from serfdom, to the "bloodlands" of Eastern Europe during World War II, to the Siberian hinterlands where Anna spent almost two decades in exile before receiving the rare opportunity to emigrate from the Soviet Union in the 1960s. In the course of her research, Megan encounters essential and sometimes disturbing aspects of recent Ukrainian history, such as Nazi collaboration, the rise and persistence of Ukrainian nationalism, and the shattering impact of Russia's full-scale invasion in 2022. Yet her wide-ranging inquiries keep leading her back to universal questions: What does family mean? How can you forge connections between generations that span different cultures, times, and places? And, perhaps most hauntingly, how can you best remember a complicated past that is at once foreign and personal?'A painfully honest and carefully researched journey of a Ukrainian American into her family's complicated and difficult past. Anchored in the catastrophe of the Second World War and the subsequent Stalinist repression of the Ukrainian peasantry, the story flows, unexpectedly to the author herself, into the unfolding drama of the current Russian invasion. Thoughtful and beautifully written.'--Jan Gross, Princeton University, author of Neighbors: The Destruction of the Jewish Community in Jedwabne, Poland'This book is not only important, but captivating and instructive.'--John-Paul Himka, University of Alberta'Megan Buskey's blend of tireless investigation with thoughtful analysis and careful prose make this book an exemplar of the best traditions in historical writing.'--Wil S. Hylton, author of Vanished: The Sixty-Year Search for the Missing Men of World War II" --